HeRO monitoring to reduce mortality in NICU patients - Fairchild KD; Aschner JL (Dove Medical Press, 2012)
Karen D Fairchild,1 Judy L Aschner21Department of Pediatrics, University of Virginia School of Medicine, Charlottesville, VA, 2Department of Pediatrics, Vanderbilt University School of Medicine, Nashville, TN, USAAbstract: In 2011, the results of a large, multicenter, randomized clinical trial of heart rate characteristics (HeRO) monitoring in preterm infants were published. Remarkably, in approximately 3000 very low birthweight (VLBW) patients in nine neonatal intensive care units (NICUs) in the US, randomization to having the HeRO score displayed to clinicians resulted in a greater than 20% reduction in mortality compared with infants whose HeRO score was not displayed. In this trial, sponsored by the National Institutes of Health, the number needed to “treat” or monitor was 48 for each additional VLBW survivor. For extremely low birthweight infants, the number needed to monitor was 23 for each additional survivor. The HeRO score incorporates two heart rate components, decreased variability and decelerations, that occur in a variety of pathologic conditions, most notably sepsis. The HeRO score was designed as an early warning system for sepsis in NICU patients. In the clinical trial, mortality among patients with blood culture-positive sepsis dropped from 16% in controls to 10% in those whose HeRO scores were displayed. Ongoing analyses are investigating whether the HeRO score is also a useful clinical or research tool for identifying other neonatal pathologies, such as necrotizing enterocolitis and acute brain injury. The purpose of this review is four-fold: (1) to provide clinicians with a background on the physiology of heart rate regulation in health and disease, (2) to describe how HeRO monitoring was developed, (3) to review results of the randomized clinical trial, and (4) to discuss use of the HeRO monitor for early detection of potentially catastrophic illness in preterm infants in the NICU.Keywords: heart rate variability, neonatal sepsis, preterm infant mortality